Transapical beating-heart chordae implantation in mitral regurgitation: a new horizon for repairing mitral valve prolapse - Lancellotti, Patrizio; Radermecker, Marc; Durieux, Rodolphe; Modine, Thomas; Oury, Cécile; Fattouch, Khalil (Journal of Thoracic Disease; Vol 8, No 12 (December 31, 2016): Journal of Thoracic Disease, 2016)
Mitral regurgitation (MR) is increasingly prevalent in western countries despite reduced incidence of rheumatic disease (1,2). MR results from several heterogeneous conditions, including disorders of the valve leaflets, mitral annulus, chordae tendineae, papillary muscles and left ventricle (LV). MR causes are roughly classified as primary (i.e. organic/structural) or secondary (i.e. functional/non-structural) (3).